Macronutrient Intake and Obesity In Adolescents: A Meta-Analysis Study - Ainun, Nur; Simbolon, Demsa (Media Gizi Indonesia, 2024)
Obesity is a condition with excess body fat due to an imbalance in energy intake consumed more than the physical activity expended. Adolescents who are obese can increase the risk of degenerative diseases. This study aimed to determine the relationship between macronutrients, including carbohydrate, protein, and fat intake, and obesity in adolescents. This study uses a meta-analysis method. Articles were taken from Google Scholar, PubMed, and Science Direct databases. The articles analyzed were articles published from 2000 – 2022, full text; the keywords used for the search were "carbohydrate”, "protein”, "fat”, "obesity, and "adolescents”. The articles were collected using PRISMA diagram and analyzed by Review Manager Application 5.4. With the fixed effect model and random effect model. From the results of this study, seven articles were identified. The results of the forest plot show the relationship between carbohydrate intake and obesity in adolescents, p-value < 0.001; OR = 2.58, protein intake with obesity in adolescents obtained p-value = 0.02; OR = 2.92, and fat intake with obesity in adolescents obtained p-value < 0.001; OR = 6.20. The conclusion of this study shows that the variables of carbohydrate, protein, and fat intake have a significant relationship with obesity in adolescents.